(untitled) (Singapore, 1996)
Advances in Information Storage Systems (AISS) series was initiated by ASME Press. New York with a first issue published in April 1991. ASME Press published a total of five volumes in 1991-93. In 1994, World Scientific Publishing Co. Private Limited took over the highly respected series and published volume number 6 in 1995. This volume number 7 is the second volume published by the World Scientific Publishing. The aim of the series remains to report the latest results from around the world in all the electromechanical, materials science, design, and manufacturing problems of information storage systems (magnetic and optical). All articles in each volume are of international archival quality refereed according to rigorous journal standards by the editors and their reviewers. The series will continue to be published with a frequency of one per year.One hundred and fifty five articles have been published in the first six volumes. This volume contains twenty seven articles that cover various aspects of information storage and processing industry organized into three parts: Micromechanical Characterization of Component Materials; Mechanics and Tribology for Data Storage Systems; Dynamics and Controls for Data Storage Systems.
Keywords: Management information systems,Information storage and retrieval systems,Quản lý hệ thống thông tin,Lưu trữ thông tin và hệ thống khôi phục